Seroprevalence of West Nile and dengue virus in the human population of the Bolivian Chaco. Issue 1 (7th September 2018) - Bartoloni, Alessandro; Remoli, Maria Elena; Farchi, Francesca; Zammarchi, Lorenzo; Fortuna, Claudia; Benedetti, Eleonora; Ciufolini, Maria Grazia; Macchioni, Fabio; Rojas, Patricia; Lara, Yunni; Padilla, Claudia; Roselli, Mimmo; et al.
Abstract : To determine the seroprevalence of antibodies against dengue virus (DENV) and West Nile virus (WNV) in the human population of the Bolivian Chaco, we tested 256 inhabitants of two rural communities. The seroprevalence, confirmed by plaque reduction neutralization test, was 7.8% and 2.7% for DENV and WNV, respectively.